SECRETORY IMMUNIGLOBULIN A AND INTELEUKIN 1- MARKERS USED IN THE DIAGNOSIS OF PERIODONTAL DISEASE - Caraiane Aureliana; Victoria Badea; Cristina Nuca; Florin Ciprian Badea; Mircea Grigorian (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study The aim of this study is to quantify secretory immunoglobulin A (IgAs) and interleukin 1 (IL1) in saliva, and to establish a possible link between the values of this two parameters and periodontal health. Material and methods Were assessed clinically oro-dental 30 subjects which were divided into 3 groups: healthy, gingivitis and with chronic periodontal disease (CPD). Saliva was collected according to the recommendations of the World Health Organization and quantitative determinations of IgAs and IL-1 were made by ELISA. Results The results show that the values of the two parameters progressively increase in patients with gingivitis and periodontitis, compared to those oro-dental clinically healthy. The study results demonstrate statistically significant differences on values of IL-1 and IgAs in patients with CPD (IgAs 317.92±45.57 mg/mL, IL-1 46.55±38.62 pg/mL) compared with those with gingivitis (IgAs 156.88±31.22 mg/mL, IL-1 40.19±17.04 pg/mL) and healthy (IgAs 151.50±38.73 mg/mL, IL-1 9.84±6.79 IL1 pg/mL). Conclusions IgAs and IL-1 can be used as markers to assess periodontal status.